Clinical Cases: Diagnostic Errors of Mastocytosis Cutaneous Forms in Children - Lianna K. Aslamazyan; Kamilla E. Efendieva; Anna A. Alekseeva; Julia G. Levina; Alina R. Pankova (Union of pediatricians of Russia, 2022)
Background. Mastocytosis refers to the group of rare diseases with pathological mast cells accumulation in tissues. Although diagnosis of cutaneous mastocytosis is not usually difficult for experienced physicians, misdiagnosis is possible.Clinical cases description. The authors describe two clinical cases of patients with mastocytosis cutaneous form, observed due to the skin rashes and without any correctly established diagnosis.Conclusion. Patients with mastocytosis require specific living conditions and regular dynamic monitoring to prevent disease progression and complications development.